Analysis of the clinical features and the risk factors of severe adenovirus pneumonia in children - Huang, H (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2021)
Objective: To analyze the clinical characteristics, risk factors for critical illness and death of severe adenovirus pneumonia in children, so as to provide clinical evidences for early diagnosis and reliable treatment. Methods: A total of 75 pediatric cases with severe adenovirus pneumonia admitted to Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology from January to October 2019 were studied. The clinical features, laboratory and imaging data, therapeutic approaches, efficacy of the treatments and prognosis were investigated retrospectively. Patients were divided into severe group and critical group. Chi square test and Mann-Whitney U rank sum test were used to analyze the data of the two groups. The risk factors for critical illness and death were analyzed by univariate and multivariate Logistic regression. Results: Among the 75 children, there were 52 males and 23 females, aged from 3 months to 8 years, including 30 of severe cases and 45 of critical case. The positive rate of adenovirus antigen in nasopharyngeal swab was 21% (15/72), and the positive rate of serum adenovirus IgM antibody was only 13% (10/75). However, the positive rate of adenovirus nucleic acid in nasopharyngeal swab was 75% (21/28). What is more, the positive rates of metagenomics next generation sequencing (mNGS) in plasma and bronchoalveolar lavage fluid were 92% (33/36) and 96% (54/56), respectively, of which 95% (63/66) were confirmed as adenovirus type 7. Relatively high dose of ribavirin and integrated therapeutic approaches (respiratory support, glucocorticoids, immunoglobulin and organ supportive therapies) were used. The recovery rate was 77% (58/75), the improvement rate was 8% (6/75) and the mortality rate was 15% (11/75). The proportion of children with the duration of fever longer than 3 days after ribavirin treatment in the critical group was significantly higher than that in the severe group(51% (18/35) vs. 8% (2/26), χ2=12.949, P<0.05). The risk factors for critical illness were younger than 4 years, longer duration of fever before and after admission to PICU, oxygenation index<300 mmHg (1 mm Hg=0.133 kPa), ferritin>1 000 μg/L, lactate dehydrogenase (LDH)>1 500 U/L, 5 lung lobes involvement, pleural effusion and (or) air leakage (all P<0.05). Among them, 5 lung lobes involvement was the independent risk factor for critical illness (adjusted OR=49.641, 95%CI 4.186-588.618, P=0.002). Risk factors for death included longer duration of fever after being admitted to PICU, oxygenation index<100 mmHg, ferritin>2 000 μg/L, interleukin (IL)-6>100 ng/L, LDH>1 500 U/L, pleural effusion and (or) air leakage (all P<0.05). Among them, IL-6>100 ng/L was the independent risk factor for the mortalities of critically ill children (adjusted OR=16.094, 95%CI 2.059-25.787, P=0.008). Conclusions: The mortality rate of severe pediatric adenovirus pneumonia caused by adenovirus type 7 is high. High positive rates of adenovirus nucleic acid in nasopharyngeal swabs and mNGS in plasma or bronchoalveolar lavage fluid contribute to early diagnosis, and mNGS can also be used for serotyping. Younger children under 4 years of age, persistent fever, extensive pulmonary lesions and significantly increased inflammatory cytokines such as IL-6 are warning indicators for critical illness and poor prognosis. Relatively high dose of ribavirin combined with integrated therapeutic approaches are beneficial for prognosis